Analisis Assesment Akademik dan Perkembangan dalam Menangani Siswa Slow Learner SDN Bojong 1 Pinang Kota Tangerang - Fadhillah, Septy Nur; Rahmanda, Farah Putri; Anggraeni, Serly; Damayanti, Dini; Salsabila, Putri; Hilmiyah, Zulfah; Utari, Aprilia Tri; Apriansyah, Fiqih (TSAQOFAH, 2022)
This study aims to analyze academic assessment and teacher development in dealing with slow learner grade II elementary school students. A slow learner is one type of child with special needs, or what is called a disability, has different learning needs in general and tends to experience learning barriers. Therefore, teachers need to require appropriate assessments, therefore the selected assessments are academic assessments and developmental assessments. This research is a qualitative research with case study method design. Data collection techniques in this study are by means of interviews, documentation and observation. The validity of the data used in this study is using source triangulation and technical triangulation. Source triangulation means that researchers obtain data from different sources using the same technique. While technical triangulation, the data obtained in the field will be compared and checked from interviews, documentation and observations conducted at State Elementary School Bojong 1 Pinang, Tangerang City. The data sources used are documents and interviews with teachers at State Elementary School Bojong 1 Pinang, Tangerang City, with research results obtained during observations from class teacher resource persons for students who have special needs before registering first conduct a psychological check to check the IQ of the students who register whether it is in accordance with the provisions of the school, then a statement from the special supervisor teacher for the process of knowing in addition to psychology, it is also based on statements from homeroom teachers who are in the classroom seen from the learning outcomes of students. Because State Elementary School Bojong 1 Pinang has just been established by the government in 2022 in January.